Faktor-Faktor Yang Mempengaruhi Impulsive Buying Secara Online: Studi Kasus Pada Generasi-Z Di Fakultas Ekonomi dan Bisnis Universitas Jambi - Dina Busyiro; Etik Umiyati; Rosmeli (Jurnal Riset Multidisiplin Edukasi, 2025)
The rapid development of digital technology has significantly transformed consumer behavior, particularly among younger generations who are deeply engaged in online activities. One of the most prominent phenomena emerging from this shift is the rise of impulsive buying behavior on various e-commerce platforms. This study aims to examine the influence of gender, price discounts, and income on impulsive buying behavior among Generation Z students at the Faculty of Economics and Business, University of Jambi. Employing a quantitative approach with an explanatory research design, primary data were collected through questionnaires distributed to 119 respondents selected using cluster sampling. The data were analyzed using multiple linear regression with the aid of SPSS version 22. The findings reveal that price discounts and income have a positive and significant effect on impulsive buying behavior, while gender shows no significant influence. These results suggest that economic factors and digital marketing strategies play a crucial role in shaping the consumer behavior of young people in the digital economy era.